Vloga ekološkega kmetovanja na zavarovanih območjih Slovenije - Blatnik, Matej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
Protected areas are known for their cultural heritage and/or their natural landmarks, but the protection brings some special measures, which often represent obstacles for development of those areas. Agriculture is also a part of those protective measures and it is increasingly transformed into organic farming. This paper is based on organic farming research, itćs development and its role in protected areas. For this purpose, we have chosen three importaint protected areas in Slovenia: Triglav National Park (TNP), Kozjansko Regional Park (KRP) and Goričko Landscape Park (KPG). Results were gathered by interviewing people, responsible for development of agriculture in those protected areas.
Keywords: agrarna geografija; ekološke kmetije; ekološko kmetijstvo; environmental protection; Slovenia; Slovenija; sustainable development; trajnostni razvoj; varstvo okolja; zavarovana območja